Can school policing be trauma-informed? Lessons from Seattle. Issue 3 (15th August 2016) - Gill, Charlotte; Gottfredson, Denise; Hutzell, Kirsten
Abstract : Purpose: The purpose of this paper is to describe Seattle's School Emphasis Officer (SEO) program, a distinctive approach to school policing that aims to connect at-risk students with services and has potential to incorporate a trauma-informed approach. Design/methodology/approach: Using qualitative data collected from a process evaluation of SEO, including interviews, observations, and analysis of activity logs and program documentation, the authors explore elements of the program that could be adapted for the development of a trauma-informed policing (TIP) model and highlight some potential pitfalls. Findings: SEO activities align well with trauma-informed principles of safety, promoting collaboration, and impulse management and are delivered in a context of trust-building, transparency, and responsivity. However, the program is poorly defined and has limited reach, has not been rigorously evaluated, and faces serious threats to sustainability. Research limitations/implications: This study does not assess the effectiveness or appropriateness of TIP. A rigorous evaluation is needed to improve upon and test the model to ensure that increased contact between police and youth is effective and does not contribute to the school-to-prison pipeline. Originality/value: To the authors' knowledge, this paper is the first to describe a potential framework for TIP and lay out an agenda for further research and policy development around this idea.